Distribution of Amphotericin B-Arabinogalactan Conjugate in Mouse Tissue and Its Therapeutic Efficacy against Murine Aspergillosis - Falk, Rama (American Society for Microbiology, 2004)
The pharmacokinetic characteristics and tissue distribution of a novel water-soluble, nontoxic amphotericin B-arabinogalactan (AMB-AG) conjugate exhibited distinct differences from those of micellar and liposomal amphotericin B formulations. These differences included extended persistence of drug in the body and its accumulation in the lungs; thus, the AMB-AG conjugate was highly effective in treating systemic murine aspergillosis.